The place of innovation law in the modern system of law - Fronchko, Volodymyr (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Innovation law in the modern legal system of Ukraine needs its new complex formation and harmonization in a single legislative system. The basis of this process should be a special innovation law that will regulate both private and public innovation processes within the integrated field of law - the Ukrainian innovation law